Effect of tillage methods and sowing dates on growth, yield and yield attributes of newly released Basmati rice (Oryza sativa L.) varieties under direct seeded - Tolma, Tayshi; Singh, Mahender; Gupta, Vikas (ORYZA-An International Journal of Rice, 2023)
To standardize the tillage methods and dates of direct seeded Jammu Basmati rice varieties under sub tropical condition, a field experiment was conducted at research farm of Agrometeorology Section, Division of Agronomy, SKUAST-J, Chatha, Jammu during kharif season 2020. The experiment was comprised of two tillage methods i.e. zero (T1) and conventional tillage (T2) , two direct sowing dates viz., 10th (D1) and 25th June (D2) along with four newly released Basmati rice varieties viz., Jammu Basmati-370 (V1), Jammu Basmati-118 (V2), Jammu Basmati-138 (V3) and Jammu Basmati-123 (V4) with 16 treatment combinations and three replications in split-split plot design. Various crop growth parameters (plant height, LAI and above ground dry matter accumulation) were recorded at fortnight interval starting from 30 DAS till physiological maturity of crop was attained. Jammu Basmati rice varieties sown under conventional tillage method recorded significantly higher number of tillers/m2 (232.7) and also effective tillers/m2 (222.7) than the zero tillage method. The 10th June sown crop observed significantly higher leaf area index, dry matter accumulation, yield and yield attributes compared to late sown crop. Crop sown under conventional tillage method realized significantly higher grain yield (23.74 q/ha) as compared to zero tillage method (18.03 q/ha). Among the varieties, Jammu Basmati-123 recorded significantly higher leaf area index, dry matter accumulation and grain yield followed by Jammu Basmati-118, Basmati-370 and Jammu Basmati-138.